Effects of dietary lysine, methionine, and tryptophan on regulating GH-IGF system and modulation of inflammatory and immune response in Pangasius bocourti - Razia Liaqat; Shafaq Fatima; Wajeeha Komal; Qandeel Minahal (PLoS ONE, 2025)
The present study assessed the effects of methionine, lysine, and tryptophan on the growth performance, amino acid composition, and immune-related gene expression of basa catfish (Pangasius bocourti). Fish (n = 260; initial weight = 10.00 ± 1.00 g) were fed eight isonitrogenous (30%) diets, each containing different combinations of tryptophan (Trp), methionine (Met), and lysine (Lys) (A0: no amino acids, A1: Trp, A2: Lys, A3: Met, A4: Trp + Met, A5: Lys + Trp, A6: Met + Lys, A7: Lys + Trp + Met, 6 g/kg each) for 10 weeks. The experiment consisted of eight treatments, each with three replicates (n = 15/replicate). After the 10-week feeding trial, the fish were intraperitoneally injected with 0.2 mL of Streptococcus iniae for a 14-day bacterial challenge. Following the feeding trial and bacterial challenge, growth parameters, insulin-like growth factor-I, haematological profile, blood biochemistry, interleukin-6, and interleukin-10 revealed that amino acid supplementation significantly improved both growth and immune response in all treatments except A0. Significant differences were observed in crude protein and amino acid profiles across treatments. Interleukin-10 levels were significantly elevated in all treatments except in the positive control (+ve A0). Compared to the positive control, interleukin-6 levels were significantly reduced (P < 0.05) in all treatments. Superoxide dismutase and catalase activity increased in response to the bacterial challenge, while malondialdehyde levels gradually decreased. The A7 diet (Lys + Trp + Met: 6 g/kg) yielded the most favourable results, enhancing the immune response, which may further support the commercial production of Pangasius bocourti.